Odporność drewna buka zwyczajnego (Fagus sylvatica L.), z drzew o zróżnicowanym stanie zdrowotnym, na rozkład powodowany przez grzyby - Szczepkowski, Andrzej (Leśne Prace Badawcze, 2010)
In the paper natural resistance of wood of healthy and damaged European beech ( Fagus sylvatica L.) trees to the activity of wood decaying fungi producing a white rot – Fomes fomentarius (L.) J. J. Kickx and Trametes versicolor (L.) Lloyd and a brown rot – Coniophora puteana (Schumach.) P. Karst was examined. The wood samples came from stands aged 80–145 bearing signs of decline and excessive self-thinning of beech trees. The stands were located in three forest districts situated in the lowland and three – in the upland/highland region, representing Poland’s main sources of beech wood. Two healthy and damaged sample trees were collected from each stand. Wood samples cut out from the trunk at the butt-end of beech trees were used for analysis. The wood decay test was done according to the norm PN-EN 350-1. After sixteen weeks of incubation, the wood of damaged trees was decayed to a larger extent than that of healthy ones by all three test fungal species. The mean loss of the wood mass from healthy and damaged trees caused by C. puteana was 28.6 and 29.7 per cent, by T. versicolor – 23.3 and 25.0 per cent and by F. fomentarius – 18.5 and 20.8 per cent, respectively. The statistically significant difference (Mann-Whitney test) of 1.1 per cent on wood loss was detected only for the wood decayed by C. puteana . Analysis of tree pairs showed a lower resistance of the wood from damaged trees in comparison with healthy ones to the decay caused by the fungi in the majority of the examined beech provenances. No geographical variability in wood mass was found between healthy and damaged trees caused by the activity of the test fungi.